2014
DOI: 10.1128/aem.03939-13
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Targets as Potential Indicators of Diesel Fuel Toxicity in Subantarctic Soils

Abstract: cAppropriate remediation targets or universal guidelines for polar regions do not currently exist, and a comprehensive understanding of the effects of diesel fuel on the natural microbial populations in polar and subpolar soils is lacking. Our aim was to investigate the response of the bacterial community to diesel fuel and to evaluate if these responses have the potential to be used as indicators of soil toxicity thresholds. We set up short-and long-exposure tests across a soil organic carbon gradient. Utiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 61 publications
4
54
0
Order By: Relevance
“…This trend was expected and observed across all diesel fuel concentration ranges and methods utilised. Within the high diesel fuel soils, both the cultivation dependent and independent methods recovered Pseudomonas and Rhodanobacter , while the SSMS and total soil communities also recovered Dyella and Parvibaculum 891011. The selective pressure from the addition of diesel fuel also reduced the total species richness, evenness and diversity within the soils, as calculated by Shannon, Simpson, and Pileu diversity indices (Fig.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This trend was expected and observed across all diesel fuel concentration ranges and methods utilised. Within the high diesel fuel soils, both the cultivation dependent and independent methods recovered Pseudomonas and Rhodanobacter , while the SSMS and total soil communities also recovered Dyella and Parvibaculum 891011. The selective pressure from the addition of diesel fuel also reduced the total species richness, evenness and diversity within the soils, as calculated by Shannon, Simpson, and Pileu diversity indices (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…They constitute the bulk of the biomass in polar soils and as such, are primarily responsible for ecosystem services such as decomposition, mineralisation, inorganic nutrient turnover and pollutant removal4. Rapid sequencing through the use of next generation sequencing (NGS) platforms have evaluated the impact of petroleum hydrocarbons on bacterial community diversity in mangroves5, oil fields6, the Gulf of Mexico following the Deepwater Horizon oil spill7 and contaminated soils in the sub-Antarctic8. It has been consistently demonstrated that the presence of petroleum hydrocarbons shift the phylogenetic make up of communities91011.…”
mentioning
confidence: 99%
“…Schafer et al (2007) identified soil biogeochemical toxicity end-points based on sensitivity of nitrification, denitrification, carbohydrate use and total soil respiration at Macquarie Island. Similarly, through dose-response modelling of the bacterial amoA gene, Van Dorst et al (2014) determined an average effective concentration responsible for a 20% change in phylogenetic diversity of 155 mg/kg as an indicator of soil health at Macquarie Island. In addition, microbial gene abundance has also been recently investigated for the development of remediation guidelines in polar soils (Richardson et al 2014).…”
Section: Bioremediationmentioning
confidence: 99%
“…In addition, they contain a high number of quantifiable phenotypes induced by a large number of environmental alterations. There are several examples of bioindicators used to determine the quality of soil 33 , water 32 and air 34 .…”
Section: Synthetic Biosensors and Environmental Qualitymentioning
confidence: 99%
“…Microbial bioindicators have been traditionally used for decades in order to estimate the altered environmental conditions and identify and quantify the effect of different pollutants in the environment [32][33] . Microorganisms have been mainly selected as bioindicators because they can be found in large quantities, which makes easier its detection and sampling.…”
Section: Synthetic Biosensors and Environmental Qualitymentioning
confidence: 99%